(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Arterial blood pressure is determined by cardiac output and peripheral vascular resistance; these parameters are finely regulated through the renin–angiotensin–aldosterone system, the sympathetic nervous system, renal sodium–water handling, and endothelial mediators. For this reason, the pharmacology of hypotensive (blood-pressure–lowering) and hypertensive (blood-pressure–raising, pressor) agents cannot be reduced to the simple idea of “lowering or raising the number”: such agents influence the heart, kidneys, brain, and peripheral vessels through different pathways and serve distinct goals in acute and chronic clinical settings